Does financial integration enhance economic growth in China? - Duc Hong Vo; Anh The Vo; Chi Minh Ho (Economies, 2020)
China is a fascinating country in Asia, the second-largest economy in the world, with incredible economic growth and development in the last two decades. In addition, China has dramatically enjoyed a disciplined and successful financial integration with the region and the world in the same period. As such, it is interesting to examine a potential link between economic growth and financial integration in this most populous country. This paper was conducted to identify whether financial integration fosters Chinese economic growth. The Auto-Regressive Distributed Lags (ARDL) model is selected, utilizing the most updated data on a globalization (or integration) index. Two distinct aspects of financial integration, the de facto (proxied for economic activities) and the de jure (proxied for the Government policies leading to integration), are considered in this paper. We apply an econometric technique, using yearly aggregated data, to examine a long-term co-integration and a causal relationship between financial integration and economic growth in China. Findings from this paper indicate a long-term co-integration between financial integration de facto and economic growth in China. The bidirectional causality between financial integration and economic growth in China is also confirmed using the Granger causality test.
Keywords: F15; F36; F43; 330; financial integration; economic growth; long-term co-integration; China